If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + f = 70 Solving 6 + f = 70 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + f = 70 + -6 Combine like terms: 6 + -6 = 0 0 + f = 70 + -6 f = 70 + -6 Combine like terms: 70 + -6 = 64 f = 64 Simplifying f = 64
| x+51+x+61+80=180 | | 15+n=1 | | 11m=-209 | | 16x^2+66x+35=0 | | 20.8-90= | | -8+x^2+(-6x)=0 | | -16+x-6x=6x-7x | | 125x=-2x | | 160x^2+340x+150=0 | | 4(3x-4)+2x=-(7x+3) | | v+4=4+v | | -3k-24=-2-3(7+k) | | 20x^3+62x^2-28x=0 | | 6y+10y=4 | | 3cos^3(3x^2)=y | | x^2+x^2=90 | | Y^2-14y+x=-41 | | 15+-77= | | 13w-4w=36 | | 140=10r | | 8x+13y=7 | | 0=4b+8b | | 21m^2-m-10=0 | | x+2x+(-x)=-2x+4 | | x^3+7x^2-6x-72=0 | | 3y+13+5y-5+2y-2= | | 128=2n | | 3ln(2x+6)=20 | | 7(-5-8)=0 | | cosx+secx=0 | | 135=-9n | | 4(6w-9)=156 |